(3jfGHjY GdMce heMGSf GdBOGH hGdTjes - (3CHj GdehGgH CMeO GdMSfj Hf jMji Hf Ydj Hf eMeO GdGQejhfj GdeQLhTjs
(3ChdgG (B:s
(3hHYO, ajbhd NGOe GdSfI GdCQejhfj Hf GdeQLhTj Ef CLd GdYdhe bOQkG hCYXegG NWQkG s
(3BNQgG (B:s
(3aGdeQA jgOj Ydi ebOGQ bjeJg, hGdfed ojYPQ aj GdbOQ GdPj MedG hCfG CSGd Gddg Cf ojdHS gPG GdcJGH KhH GdbHhd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B186 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs